PENGARUH FREKUENSI ISTIGHFAR TERHADAP TINGKAT KECEMASAN PADA MAHASISWA FAKULTAS DAKWAH DAN KOMUNIKASI - Purwanti, Kirani Sarah; Rohman, Ujang; Ismail, Shalahudin (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to examine the relationship between the frequency of istighfar and the anxiety levels among students of the Faculty of Da’wah and Communication at Sunan Gunung Djati State Islamic, Bandung. The research adopts a quantitative approach using survey methods, involving 50 respondents selected through purposive sampling. The instrument used was a 4-point Likert scale questionnaire measuring the frequency of istighfar (independent variable) and student’s anxiety levels (dependen variable). The findings that the data followed a normal distribution based on the normality test. A simple linear regression analysis yielded an F-value of 7.382 with a significance level of 0.009, indicating a significant relationship between the two variablrs the R Square value of 0.133 shows that the frequency of istighfar accounts for 13.3% of the variance in anxiety levels, with the remaining 86.7% attributed to other external factors. This research supports the notion that spiritual activities such as istighfar can help alleviate anxiety, though its contribution is relatively small. Therefore, spiritual- based approaches can be one the methods applied in managing students’ mental health but should be complemented, for more optimal results.